2023
DOI: 10.1002/ptr.7932
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic effects of natural products and herbal extracts on nonalcoholic fatty liver disease/nonalcoholic steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common condition that is prevalent in patients who consume little or no alcohol, and is characterized by excessive fat accumulation in the liver. The disease is becoming increasingly common with the rapid economic development of countries. Long‐term accumulation of excess fat can lead to NAFLD, which represents a global health problem with no effective therapeutic approach. NAFLD is a complex, multifaceted pathological process that has been the subject of extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 283 publications
(307 reference statements)
0
4
0
Order By: Relevance
“…In recent years, multiple studies have indicated that a combination of traditional Chinese and Western medicine in treating NAFLD is more effective than Western medicine alone in improving abnormal liver function, reducing blood lipids, and enhancing insulin resistance, among other aspects. [ 10 , 11 ] Based on this, our study includes randomized controlled trials of traditional Chinese medicine in combination with Silymarin capsules for the treatment of NAFLD in accordance with the standards. We intend to use meta-analysis and systematic evaluation to explore the clinical efficacy and quality assessment of traditional Chinese medicine in combination with Silymarin in the treatment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multiple studies have indicated that a combination of traditional Chinese and Western medicine in treating NAFLD is more effective than Western medicine alone in improving abnormal liver function, reducing blood lipids, and enhancing insulin resistance, among other aspects. [ 10 , 11 ] Based on this, our study includes randomized controlled trials of traditional Chinese medicine in combination with Silymarin capsules for the treatment of NAFLD in accordance with the standards. We intend to use meta-analysis and systematic evaluation to explore the clinical efficacy and quality assessment of traditional Chinese medicine in combination with Silymarin in the treatment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Flavonoids are plentiful in diverse natural sources and have been documented to yield considerable therapeutic benefits in NAFLD by engaging multiple pathways. 22 Mechanistic research demonstrated that flavonoids present in snow chrysanthemum targeted the Sirt1/PPARγ pathway to regulate hepatic glucose and lipid metabolism. 23 Another research showed that the flavonoids present in Eucommia ulmoides leaves could potentially decrease lipid levels by regulating PPARγ expression via induction of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many natural products have been found to have the effect of regulating the intestinal liver axis and improving fatty liver. These natural products are mainly effective by affecting intestinal microbiota, bile acid metabolism, inflammatory reactions and other ways ( Cao et al, 2023 ). This article presents a comprehensive review of how metabolites derived from natural products influence the gut microbiota composition.…”
Section: Introductionmentioning
confidence: 99%